2014
DOI: 10.3389/fpsyg.2014.01195
|View full text |Cite
|
Sign up to set email alerts
|

Probability cueing of distractor locations: both intertrial facilitation and statistical learning mediate interference reduction

Abstract: Targets in a visual search task are detected faster if they appear in a probable target region as compared to a less probable target region, an effect which has been termed “probability cueing.” The present study investigated whether probability cueing cannot only speed up target detection, but also minimize distraction by distractors in probable distractor regions as compared to distractors in less probable distractor regions. To this end, three visual search experiments with a salient, but task-irrelevant, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
179
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(199 citation statements)
references
References 51 publications
15
179
5
Order By: Relevance
“…Considering in particular the deployment of selective attention across the visual space, the degree of interference determined by salient but irrelevant visual stimuli that appear at locations that in the past have been often associated with distracting events is reduced (Ferrante et al, 2018;Goschy, Bakos, Müller, & Zehetleitner, 2014;Leber, Gwinn, Hong, & O'Toole, 2016;Sauter, Liesefeld, & Müller, in press;Sauter, Liesefeld, Zehetleitner, & Müller, 2018;Wang & Theeuwes, 2018a; for a recent review see Chelazzi, Marini, Pascucci, & Turatto, 2019). Depending on the specific manipulations performed, these effects have been observed for relatively wide regions of the visual field (i.e., contrasting visual hemifields with high vs. low distractor frequency, as in Goschy et al, 2014;Sauter et al, 2018;in press), but also for discrete spatial locations, emerging in a graded fashion which reflected the precise statistical contingencies applied (Ferrante et al, 2018;Wang & Theeuwes, 2018a. Overall these studies suggest that suppression history may alter topographic maps of the visual space that code the attentional priority of the stimuli in the visual field (e.g., Todd & Manaligod, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Considering in particular the deployment of selective attention across the visual space, the degree of interference determined by salient but irrelevant visual stimuli that appear at locations that in the past have been often associated with distracting events is reduced (Ferrante et al, 2018;Goschy, Bakos, Müller, & Zehetleitner, 2014;Leber, Gwinn, Hong, & O'Toole, 2016;Sauter, Liesefeld, & Müller, in press;Sauter, Liesefeld, Zehetleitner, & Müller, 2018;Wang & Theeuwes, 2018a; for a recent review see Chelazzi, Marini, Pascucci, & Turatto, 2019). Depending on the specific manipulations performed, these effects have been observed for relatively wide regions of the visual field (i.e., contrasting visual hemifields with high vs. low distractor frequency, as in Goschy et al, 2014;Sauter et al, 2018;in press), but also for discrete spatial locations, emerging in a graded fashion which reflected the precise statistical contingencies applied (Ferrante et al, 2018;Wang & Theeuwes, 2018a. Overall these studies suggest that suppression history may alter topographic maps of the visual space that code the attentional priority of the stimuli in the visual field (e.g., Todd & Manaligod, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Critically, however, this appears specific to conditions that allow observers to learn, often implicitly, from statistical regularities across search displays (Chelazzi, Marini, Pascucci, & Turatto, 2019;van Moorselaar & Slagter, 2020). For example, a recent study by Wang and Theeuwes (2018) demonstrated that in a mixed-feature variant of the additional singleton paradigm, salient singleton distractors were more efficiently ignored at locations with a high distractor probability, even though almost all participants were unaware of the embedded statistical regularity (see also) (Ferrante et al, 2018;Goschy, Bakos, Müller, & Zehetleitner, 2014;Leber, Gwinn, Hong, & O'Toole, 2016). These findings add to a rapidly growing body of research that shows that distractor inhibition may not be under voluntary, top-down control, but greatly relies on expectations derived from past experience about the likelihood of events or statistical learning (Noonan, Crittenden, Jensen, & Stokes, 2018;Theeuwes, 2019;van Moorselaar & Slagter, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…When we look for a unique target object within a rich visual scene, often other objects stand out from the background of nontarget items and may capture attention before the target is attended. In such visual pop-out search tasks, observers become more efficient, over time, in minimizing the interference generated by such salient but task-irrelevant distractors when these consistently occur in certain regions of the search display (Goschy, Bakos, Müller, & Zehetleitner, 2014). However, the mechanisms underlying this learning effect, termed probability cueing of distractor locations (Goschy et al, 2014), are poorly understood: Do observers learn to suppress distractors on the basis of their likely location alone?…”
mentioning
confidence: 99%